2007
DOI: 10.1375/twin.10.1.202
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing Twin: A Possible Cause of Cerebral Impairment

Abstract: Fetal death in a twin conception during second and third trimester is associated with increased risk of cerebral injury in the surviving twin. The aim of this study is to test the hypothesis that even early fetal losses as a ‘vanishing’ twin may be associated with an increased risk of cerebral impairment in the surviving twin. The study population comprised 362 pregnant women attending Liverpool Women's Hospital recruited between 1999 and 2001. Women were classified according to the first ultrasound scan into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Given that about 1/8 of all natural pregnancies are initially multiple with subsequent spontaneous early loss of one or more foetuses (vanishing twin phenomenon), it has been suggested that a significant proportion of singletons with spastic CP may be the result of the death of a co-twin in the second half of gestation [18]. In monochorionic twin pregnancies, the death of one twin late in gestation is recognized as being an important risk factor for the surviving co-twin to have CP.…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 99%
“…Given that about 1/8 of all natural pregnancies are initially multiple with subsequent spontaneous early loss of one or more foetuses (vanishing twin phenomenon), it has been suggested that a significant proportion of singletons with spastic CP may be the result of the death of a co-twin in the second half of gestation [18]. In monochorionic twin pregnancies, the death of one twin late in gestation is recognized as being an important risk factor for the surviving co-twin to have CP.…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 99%
“…If the reported cases are applicable to the general population, the excessively high frequency of calculated twin gestations is surprising. Two searching papers by Anand et al ( 2007 ) attempted to ascertain whether vanished twins had any signi fi cant effect upon the cerebral capacity of the survivor. No unequivocal results were obtained.…”
Section: Vanishing Twin Phenomenonmentioning
confidence: 99%
“…[11] Different anastomotic channel are seen -artery to artery, artery to vein, vein to vein. Complication that occurs are twin to twin transfusion syndrome, discordant twin, cerebral palsy, porencephaly microcephaly, multicystic leukomalacia [12][13]. Neurological damage is most likely caused by ischemic necrosis leading to cavitary brain lesions.…”
Section: Discussionmentioning
confidence: 99%